Fibroblast growth factor-10 and epithelial-mesenchymal transition in colorectal cancer - Farajihaye Qazvini, Fatemeh (EXCLI J, 2019)
As an inducer of epithelial-mesenchymal transition (EMT), fibroblast growth factor-10 (FGF-10) has a role in cell proliferation and differentiation in the embryo in addition to invasion and metastasis during carcinogenesis. In this study, we aimed to investigate the FGF-10 gene expression in tumor tissues based on the pathological feature of tumor related to EMT and metastasis. 62 tumors were obtained from 62 colorectal cancer patients during surgery. The pathological characteristics of the patients were carefully collected and classified by Iran National Tumor Bank. To quantify FGF-10 gene expression, RNA extraction, reverse transcription-PCR and real-time PCR were respectively performed. In addition, three colorectal cancer cell lines including LS174T, SW-948 and SW-480 were collected and cultured for further molecular analysis. Consequently, FGF-10 gene expression showed increased expression level in LS174T and SW-948 while it displayed decreased level in SW-480. Considering the tumor samples, we found an upregulation of FGF-10 gene expression in 52.1 % of all tumors in stage III and only in 9.09 % of all tumors in stage I. Also, there were an upregulation of FGF-10 gene expression in 50 % of all positive lymph invasion patients. Besides, FGF-10 gene upregulation was observed in 50 % of all tumors with a size larger than 5 cm (P value < 0.05) and 69 % of all tumors located in the colon (P value < 0.05). To our knowledge, this is the first time that FGF-10 expression is reported based on pathological features of colorectal cancer.